Legal Analysis of the Utilization of Stem Cells in Medical Practice - K.Suryana; L.Wibisana (The Medical Journal of Hospital Management and Health Law, 2025)
Introduction: The rapid advancement of biomedical technology has positioned stem cell therapy as a revolutionary frontier in modern medicine, offering unprecedented potential for regenerating damaged tissues and treating previously incurable diseases. However, this scientific leap outpaces existing legal frameworks, creating a complex intersection between medical innovation, ethical boundaries, and patient safety. Methods: This study utilizes a normative legal research method, examining statutory regulations, international human rights instruments, and doctrinal legal literature to evaluate the current regulatory landscape surrounding stem cell applications. Results: The findings reveal that while some jurisdictions have established preliminary guidelines, there remains a pervasive lack of comprehensive, binding legislation specifically governing the sourcing, clinical trials, and commercialization of stem cell therapies. This regulatory void leaves significant room for unauthorized clinical practices, exploitation of vulnerable patients, and legal uncertainty regarding liability. Discussion: The discussion integrates an extensive literature review, analyzing the tension between the therapeutic right to health and the state's duty to protect public safety from unproven interventions. It addresses the legal status of embryonic stem cells, the necessity of rigorous informed consent protocols, and the critical need for a harmonized international standard to prevent "stem cell tourism" where patients seek unregulated treatments abroad. Conclusions: In conclusion, the current legal infrastructure is inadequate to manage the dual imperatives of fostering medical innovation and preventing ethical abuses. It is highly recommended that lawmakers enact specific, adaptive legislation and establish centralized oversight bodies to balance therapeutic advancements with robust legal protections.